Power System Engineering. Planning, Design, and Operation of Power Systems and Equipment - Schlabbach J. Jurgen (Weinheim, Wiley-VCH Verlag, 2014)
Uescribing in detail how electrical power systems are planned and designed, this book illustrates the required structures of systems, substations and equipment using international standards and latest computer methods.Advantages and disadvantages of the different arrangements within switchyards and of the topologies of the power systems are discussed, describing methods to determine the main design parameters of cables, overhead lines, and transformers needed to realize the supply task, as well as the influence of environmental conditions on the design and the permissible loading of the equipment. Additionally, general requirements for protection schemes and the main schemes related to the various protection tasks are given. New technical developments, such as high- temperature overhead transmission lines and technical conditions for the connection of renewable energy generation are discussed.With its focus on the requirement and procedures of tendering and project contraction, this book enables the reader to adapt the basics of power systems and equipment design to special tasks and engineering projects.